2015
DOI: 10.3389/fphar.2015.00199
|View full text |Cite
|
Sign up to set email alerts
|

Systems pharmacology of adiposity reveals inhibition of EP300 as a common therapeutic mechanism of caloric restriction and resveratrol for obesity

Abstract: Both caloric restriction (CR) and resveratrol (RSV) have beneficial effects on obesity. However, the biochemical pathways that mediate these beneficial effects might be complex and interconnected and have not been fully elucidated. To reveal the common therapeutic mechanism of CR and RSV, we performed a comparative transcriptome analysis of adipose tissues from diet-induced obese (DIO) zebrafish and obese humans. We identified nine genes in DIO zebrafish and seven genes in obese humans whose expressions were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Among the potential upstream regulators with increased activity that may represent adipocyte treatment targets was SYVN1, which has a role in the regulation of endoplasmic reticulum protein degradation, and was shown to increase body weight by interacting with peroxisome proliferatoractivated receptor γ, coactivator 1β (PGC1β) in mice [48]. Potential upstream regulators with decreased activity were FOXA1, a transcription factor that has been implicated in the development of obesity [49], and the energy sensor AMPK. These potential treatment targets warrant further investigation, since our study design cannot distinguish whether altered expression levels are due to obesity or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the potential upstream regulators with increased activity that may represent adipocyte treatment targets was SYVN1, which has a role in the regulation of endoplasmic reticulum protein degradation, and was shown to increase body weight by interacting with peroxisome proliferatoractivated receptor γ, coactivator 1β (PGC1β) in mice [48]. Potential upstream regulators with decreased activity were FOXA1, a transcription factor that has been implicated in the development of obesity [49], and the energy sensor AMPK. These potential treatment targets warrant further investigation, since our study design cannot distinguish whether altered expression levels are due to obesity or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has become a severe health issue globally. Resveratrol significantly decreased the body weight and fat mass in mice with HFD-induced obesity, showing reduced leptin and lipids in plasma, modulated metabolism of glucose and insulin, and restored immune dysfunction, via the activation of PI3K/SIRT1 and Nrf2 signaling pathways, and the inhibition of transcriptional regulators (e.g., EP300 gene), which are involved in the differentiation of adipocytes as well as lipid storage and metabolism [95,96]. Moreover, besides a significant dose-dependent decrease of weight gain and lipid deposition in the liver and adipose tissues of HFD-induced obese mice, low concentrations of resveratrol (1-10 µM) suppressed adipogenic differentiation in pre-adipocytes, downregulated the expression of peroxisome proliferator-activated receptor γ (PPAR-γ) and perilipin protein in differentiated adipocytes, and inhibited TNF-α-induced lipolysis in mature adipocytes [97].…”
Section: Obesitymentioning
confidence: 99%
“…This reduction in body weight and BMI was accompanied by preservation of lean mass. Orlistat inactivates gastric and pancreatic lipases, reducing fat absorption and, thus, total calorie intake , and resveratrol activates cellular pathways involved in lipid utilization and energy expenditure in metabolically active tissues . Both compounds have been used to manage body weight in subjects who have obesity ; however, we observed that the synergic activity of the O‐R combination enhanced their beneficial effects, resulting in a higher percentage of body weight loss.…”
Section: Discussionmentioning
confidence: 78%
“…In vitro and in vivo studies have demonstrated that resveratrol acts directly on adipose tissue, decreasing adiposity during obesity through a mechanism similar to that activated by calorie restriction . Moreover, the anti‐obesity action of resveratrol also involves modulation of lipid metabolism in the liver and skeletal muscle, preventing lipid accumulation and enhancing fatty acid oxidation .…”
Section: Introductionmentioning
confidence: 99%